2007
DOI: 10.1161/circulationaha.106.680678
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation to Aid Cardiopulmonary Resuscitation in Infants and Children

Abstract: Background-Extracorporeal membrane oxygenation (ECMO) has been used to support cardiorespiratory function during pediatric cardiopulmonary resuscitation (CPR). We report on outcomes and predictors of in-hospital mortality after ECMO used to support CPR (E-CPR). Methods and Results-Outcomes for patients aged Ͻ18 years using E-CPR were analyzed with data from the Extracorporeal Life Support Organization, and predictors of in-hospital mortality were determined. Of 26 242 ECMO uses reported, 695 (2.6%) were for E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
245
6
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(257 citation statements)
references
References 28 publications
4
245
6
2
Order By: Relevance
“…Our study supports a number of findings from an E-CPR study done in pediatric patients, which demonstrated that patient demographic factors such as age, weight and sex do not effect survival [6], and another paper indicating a correlation with duration of ECMO [16]. Our study also partially agrees with major conclusions from previous studies of adult E-CPR patients, which indicate that a state of acidosis is correlated with poor E-CPR outcomes [20].…”
Section: Discussionsupporting
confidence: 91%
“…Our study supports a number of findings from an E-CPR study done in pediatric patients, which demonstrated that patient demographic factors such as age, weight and sex do not effect survival [6], and another paper indicating a correlation with duration of ECMO [16]. Our study also partially agrees with major conclusions from previous studies of adult E-CPR patients, which indicate that a state of acidosis is correlated with poor E-CPR outcomes [20].…”
Section: Discussionsupporting
confidence: 91%
“…ECPR patients with a preexisting diagnosis of cardiac illness have shown improved survival outcomes, when compared with patients with noncardiac illnesses. 5,6,8,30,32 Perhaps patients with cardiac illness have less multiorgan dysfunction before cardiac arrest and therefore are more likely to…”
Section: Population Of Patientsmentioning
confidence: 99%
“…Two multicenter registry database analyses have also been performed. From the Extracorporeal Life Support Registry, Thiagarian et al [183] found that overall survival to hospital discharge after ECPR was 38%. Raymond et al [184] analyzed the National Registry of Cardiopulmonary Resuscitation and found survival to discharge of 44%, remarkably, with 95% reported having favorable neurological outcome.…”
Section: Advances In Cerebral Resuscitation In Childrenmentioning
confidence: 99%